Impacts of pharmacist-led medication reconciliation on discrepancies and 30-days post-discharge health services utilization in elderly Jordanians - Eman A. Hammad; Farah Khaled; Majed Shafaamri; Bara’ah Amireh; Rasha Arabyat; Rana K. Abu-Farha (PLoS ONE, 2025)
Objectives To assess the impacts of pharmacist-led medication reconciliation (MedRec) on medication discrepancies and post-discharge health services utilization in elderly patients in Jordan. And to identify predictors of post discharge outcomes. Method Newly admitted patients, aged above 65 years were randomly allocated into either a group receiving pharmacist led MedRec or standard care. Within 24 hours of admission, a clinical pharmacist compiled a list of the Best Possible Medication History (BPMH) using at least two sources of information. The pharmacist compared the BPMHs to the admission charts to identify discrepancies and resolved them accordingly. One month post-discharge, patients were assessed for health services use, namely hospital readmissions, emergency department (ED) visits, and adverse drug events (ADEs). Logistic regressions used to investigate predictors of post discharge outcomes. Results A total of 128 patients with 151 medication discrepancies were included: 82 (54.3%) discrepancies in the intervention group, and 69 (45.7%) in the control group. A total of 52 Pharmacist-led interventions were recommended to physicians, of which 49 (94.2%) were accepted/implemented. At discharge, the majority of unintentional discrepancies were successfully resolved (p < 0.001). At 30 days post-discharge, patients who were readmitted to the hospital and visited the ED were significantly from the control group. There was no significant difference with respect to experiencing ADEs among the study groups. Patients who received pharmacist-led MedRec had almost 70% lower likelihood of hospital readmission and ED visits. Discrepancies at discharge was associated with higher odds of hospital readmissions. Conclusion Pharmacist-led MedRec services improved continuity of care for elderly patients. Implementing a structured reconciliation process successfully resolved discrepancies and reduced hospital readmissions as well as ED visits at 30-days post-discharge. This outlines potentials for healthcare cost savings. Future studies are recommended to explore long-term benefits, cost-effectiveness, and integrating pharmacist-led MedRec into standard discharge planning.